Extension of the basic Global Health Security (GHS) index: Health system security indicator - Živković Živan; Panić Marija (Trendovi u Poslovanju)
The paper discusses the extension of the Global Health Security (GHS) index with new non-medical predictors: Gross Domestic Product (GDP) per capita as a basic indicator of economic growth, Corruption Perception Index (CPI) and Democracy Index (DI) as significant indicators of social relations. This extension of the GHS index provides a more reliable model for predicting the ability of a country's health system to provide an adequate response in a pandemic crisis when human health is seriously endangered. Evaluation of the results of the extension of the GHS index by additional non-medical predictors was performed using multiple linear regression analysis (MLRA), both for the basic and for the extended model. The obtained values of the coefficient of determination (R2) indicate that the extended GHS model shows the same high level of fitting as the basic model, which confirms the justification of its extension. The research was conducted on the basis of available data for 42 European countries.